Productivity and quality of smooth brome pastures under continuous, rotational, and mob grazing by sheep - Humerickhouse, Natalie (Kansas State University, 2014)
In recent years, an alternative grazing method to continuous and rotational methods has gained popularity among producers and has been termed mob grazing. Mob grazing uses high animal densities grazing for a short period of time. The objectives of this study were to determine the impact of continuous, rotational, and mob grazing on forage production and the quality of smooth bromegrass (Bromus inermis Leyss), along with soil dissolved organic carbon (DOC), microbial biomass carbon (MBC), and dehydrogenase enzyme activity. Twelve paddocks, 4 continuous (40 X 10 m), 4 rotational and 4 mob (15 X 10 m), were designated at the Kansas State University Sheep and Meat Goat Center in Manhattan, KS. Forage quality samples were collected by hand clipping randomly throughout the paddock. Neutral detergent fiber (NDF) and acid detergent fiber (ADF) were determined using ANKOM technology and crude protein (CP) content was calculated by multiplying total nitrogen determined by combustion by 6.25. Soil samples were extracted with 0.5 M K2SO4 and analyzed for DOC and MBC using the chloroform-fumigation-extraction method and soil dehydrogenase activity using the colorimetric method. Forage quality declined as the spring grazing season progressed in all treatments. Sheep grazed higher quality forage in the continuous and rotational treatments in the period prior to the spring mob grazing event. No treatment differences were found for DOC, MBC, dehydrogenase, or total forage biomass accumulation. Dissolved organic carbon and soil biological parameters have not been altered by the grazing management. Forage quality was found to be poorest in the mob treatment at the time of grazing. The mob treatment accumulated the greatest amount of aboveground biomass prior to grazing, however season-long total biomass accumulation was not different from the other treatments. Based on this research, in the short-term, there are no advantages of mob grazing over rotational grazing.
Keywords: Grazing management; Agronomy (0285)